2000
DOI: 10.1007/s007840000068
|View full text |Cite
|
Sign up to set email alerts
|

Using ultrasound transmission velocity to analyse the mechanical properties of teeth after in vitro, in situ, and in vivo irradiation

Abstract: Ultrasound transmission velocity (UTV) in isotropic material as a measure for the modulus of elasticity was correlated to mechanical properties. Changes in micromechanical properties of radiated teeth and influence of the oral cavity were to be evaluated nondestructively. UTV was measured in extracted teeth after 36 Gy and 62 Gy of in situ (enorally, with no contact to the oral cavity) and in vitro irradiation. Relative to controls, teeth subjected to 62 Gy in vivo showed higher UTV values for dentine and enam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1
23

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 10 publications
2
45
1
23
Order By: Relevance
“…Although irradiated dentin is a clinically relevant bonding substrate, little is known about the direct effects of ionizing radiation on dentin 1,11) . Grotz et al 30) reported that the mechanical properties of dentin seemed to be less affected by irradiation than enamel. It should be mentioned that direct radiogenic effects may affect the mechanical stiffness of dentin 8,9) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although irradiated dentin is a clinically relevant bonding substrate, little is known about the direct effects of ionizing radiation on dentin 1,11) . Grotz et al 30) reported that the mechanical properties of dentin seemed to be less affected by irradiation than enamel. It should be mentioned that direct radiogenic effects may affect the mechanical stiffness of dentin 8,9) .…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that direct radiogenic effects may affect the mechanical stiffness of dentin 8,9) . However, under radiotherapy conditions, irradiation obviously has only a minor effect on the mechanical properties of dentin 30) . Zach 31) reported that irradiated teeth showed no alterations in crystallinity or calcium-phosphorus ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the current study, the samples were placed in artificial saliva during irradiation to simulate, as precisely as possible, the conditions that are found in the oral cavity [16] . However, other media, including 0.9% saline solution [6,13] , distilled water [11,15] , or buffered phosphate solution [11] , have been used to store teeth in similar studies. Although artificial saliva does not exactly mimic the characteristics of natural saliva, especially in the case of patients undergoing head and neck radiation therapy, who present changes in the flow, secretion, and composition of natural saliva [22] , artificial saliva is still considered the most suitable storage medium [16,23] .Studies of the structural changes in enamel and dentin following irradiation are controversial [6,[11][12][13]15,16] .…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-related caries or "radiation caries" is one of the highest indirect and late effects of radiation in the head and neck region [6] . This complication is a complex and destructive disease that causes severe destruction of the tooth enamel and dentin in head and neck-irradiated patients [5,7,8] and has negative effects on their quality of life [8] .…”
Section: Effect Of Gamma Radiation On Mechanical Properties Of Tooth mentioning
confidence: 99%
See 1 more Smart Citation